Migration, Cultural Memory and Identity in Benjamin Kwakye’s The Other Crucifix - Yitah, H.; Okyerefo, M. (African Literature Today, 2016)
This paper examines the relationship between cultural memory and belongingness in Benjamin Kwakye’s novel, The Other Crucifix, and the ways in which this relationship shapes the identity of African immigrants in America. We find that Kwakye’s novel fills some thematic gaps in the African migration story. Whereas other African migration novels seem more concerned with the history and identity of groups of immigrants, Kwakye is more interested in the identity of individual characters. In addition, while North African migration narratives (and, interestingly, some of his Ghanaian compatriots) typically present illiterate or lowly educated characters who travel to Europe often via illegal means, and whereas his West African precursors are preoccupied with the return of the sojourner and his reunion with his native society, Kwakye depicts a highly educated legal immigrant, Jojo Badu, who struggles to adapt to life in America but resists acculturation on the host country’s terms. For Jojo ‘home’ and identity are defined by cultural memory which in the narrative takes the form of remnant consciousness: ‘the ontological, physical, and spiritual manifestations of reclaiming an African cultural heritage’ (McKoy 2002, 195). In The Other Crucifix home country and host country are conceived in spatial terms along a polarity in which America signifies displacement and psychic chaos while Africa represents continuity and psychic calm. This polarity reflects the changing psychology of the protagonist as he oscillates between the deep anxiety of forgetting his original culture and identity and his desire to adjust to the host society and to create a new identity.
Keywords: Migration; Identity; Cultural Memory; Crucifix